Social Forestry and Community Empowerment through Honey Bee Farming in Nagari Simarasok - Ahmad Dhany; Nora Eka Putri (The Future of Education Journal, 2026)
Social forestry is intended to integrate forest conservation with community welfare, yet its local outcomes depend on meaningful participation and capable institutions. This study analyzes community empowerment through honey bee cultivation under the social forestry program in Nagari Simarasok, Baso District, Agam Regency. A descriptive qualitative design was employed with ten purposively selected informants representing the nagari government, the Nagari Forest Management Institution (LPHN), social forestry business group members, and surrounding communities. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through data collection, reduction, display, and conclusion drawing; validity was strengthened through source and technique triangulation. The findings show that the program improved cultivation knowledge and skills, collective work, deliberative participation, and ecological awareness. An initial assistance of 35 bee hives developed into personal hive ownership among 12 group members, with approximately 18 liters of honey produced per 40-day harvest cycle, providing supplementary household income. Community involvement covered socialization, training, maintenance, forage planting, harvesting, packaging, marketing, and group decision-making. LPHN acted as facilitator, mentor, mediator, evaluator, and network builder. However, limited market reach, business legality, human-resource capacity, and weather variability constrained economic optimization. Strengthening cooperatives, legal assistance, product standardization, and digital marketing is therefore essential for sustainable empowerment.